Efﬁcacy and Safety of Methyldopa and Labetalol in the Treatment of Pre-Eclampsia - Zulfiqar Ali Khan, Sadaf Sabah, Javeria Sana Sheikh, Rida Ubaid, Rahman Shah, Zainab Karim, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Pre-eclampsia, characterized by hypertension and proteinuria in the second half of pregnancy is associated with significant mortality and morbidity throughout the world. Many antihypertensive agents have been used for the management of pre-eclampsia. Objective: To compare the efﬁcacy and safety of methyldopa and labetalol in the treatment of pre-eclampsia. Methods: This quasi experimental study was conducted at the Department of Obstetrics & Gynecology, DHQ Nowshehra. The study enrolled 54 pregnant women diagnosed with pre-eclampsia. After obtaining a detailed medical history, participants were non-randomly assigned to receive either labetalol or methyldopa. Baseline systolic blood pressure measurements were recorded for all participants. Treatment efficacy was assessed by measuring the change in SBP 48 hours after the initiation of treatment. Results: Mean age of study participants was 27.63±4.099 years. The mean baseline SBP was 168.22 ± 6.823 mmHg, which reduced to 142.83 ± 4.801 mmHg after 48 hours of treatment for the entire study population. Stratification by age did not reveal any statistically significant differences in the efficacy or safety of the two drugs (p > 0.05). Specifically, for participants aged ≤ 28 years, the SBP decreased from 168.19±7.217 mmHg to 142.96±4.903 mmHg with labetalol, and from 168.26±6.543 mmHg to 142.70±4.786 mmHg with methyldopa. Conclusion: Labetalol and methyldopa are equally effective in managing pre-eclampsia in terms of blood pressure control. Further research with larger sample sizes is recommended to confirm these findings and evaluate additional outcomes such as maternal and fetal effects. Keywords: Pre-eclampsia, hypertension, labetalol, safety, efficacy, methyldopa.